Sundanese’s children naming tradition: A descriptive case study of language maintenance and shift in Bandung - Rudi Suherman (Universitas Islam Sultan Agung, 2021)
A name given to someone may represent his ethnic background. Therefore, it is likely used by most people in recognizing where someone comes from. This study is aimed at examining the possible correlation between children’s name given by their Sundanese parents with their ethnic background in maintaining the Sundanese language in local region in Bandung, the Capital city of West java. 17 Sundanese family are involved in this descriptive case study. Both parents, representing by 17 fathers and 17 mothers, originally come from different region in west java province and have resided in Bandung for more than a decade. The data, embracing the characteristic of survey, are gained from a set of questionnaires and semi -structured interview consisting of questions related to family’s background, the name given, as well as the reason that drives them giving the names. This study has revealed the current trend on naming tradition in Bandung in which there is a shift from Sundanese, to other language particularly Arabic. This may be happened because most of the participants in this study are Muslims. Hence, Arabic as the language of Islam predominantly influence the naming tradition in Sundanese family.